Endoscopic Modified Medial Maxillectomy for Resection of an Inverted Papilloma Originating from the Entire Circumference of the Maxillary Sinus - Kota Wada; Takashi Ishigaki; Yutaro Ida; Yuki Yamada; Sachiko Hosono; Hideo Edamatsu (Case Reports in Otolaryngology)
For treatment of a sinonasal inverted papilloma (IP), it is essential to have a definite diagnosis, to identify its origin by computed tomography (CT) and magnetic resonance imaging (MRI), and to select the appropriate surgical approach based on the staging system proposed by Krouse. Recently, a new surgical approach named endoscopic modified medial maxillectomy (EMMM) was proposed. This approach can preserve the inferior turbinate and nasolacrimal duct. We successfully treated sinonasal IP with EMMM in a 71-year-old female patient. In this patient, the sinonasal IP originated from the entire circumference of the maxillary sinus. EMMM is not a difficult procedure and provides good visibility of the operative field. Lacrimation and empty nose syndrome do not occur postoperatively as the nasolacrimal duct and inferior turbinate are preserved. EMMM is considered to be a very favorable approach for treatment of sinonasal IP.